A Critical Perspective on Mechanical Testing of Implants and Prostheses. (March 2016) - Bonfante, E.A.; Coelho, P.G.
The degree of interplay among variables in dental implant treatment presents a challenge to randomized clinical trials attempting to answer questions in a timely, unbiased, and economically feasible fashion. Further adding complexity to the different scenarios is the varied implant designs and related bone response, area of implantation, implant bulk material, restoration, abutments and related screws, fixation mode (screwed, fixed, or a combination), and horizontal implant-abutment matching geometry. This article critically appraises the most common mechanical testing methods used to characterize the implant-prostheses complex. It attempts to provide insight into the process of construction of an informed database of clinically relevant questions regarding preclinical evaluation of implant biomechanics and failure mechanisms. The use of single load to failure, fatigue life, fatigue limit, and step-stress accelerated life testing is discussed with emphasis on their deliverables, weaknesses, and strengths. Fractographic analysis and challenges in the correlation between laboratory- and in-service-produced failures of dental ceramics, resin composites, and titanium are introduced. In addition, examples are presented of mechanical characterization studies used in our laboratory to assess some implant-supported rehabilitation variables.